1987
DOI: 10.1093/rheumatology/26.5.346
|View full text |Cite
|
Sign up to set email alerts
|

Anticardiolipin Antibodies in Rheumatoid Arthritis

Abstract: Anticardiolipin antibody (ACA) was present in the sera of 49% of 90 consecutive patients with rheumatoid arthritis (RA). The ACA was absent in 30 control patients with osteoarthritis. C-reactive protein levels equal to or exceeding 7 mg/dl were found in 10 patients all of whom were ACA positive. ACA was present in a larger proportion of rheumatoid factor (RF) positive than of RF negative patients. Male sex and extra-articular manifestations of RA were both more common in ACA positive than ACA negative patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 0 publications
1
11
0
1
Order By: Relevance
“…Anticaridiolipin antibodies were present in a larger proportion of RF-positive than RF-negative patients in one study [34], but there was no relationship between them in others [19,35].…”
Section: Association Between Presence Of Acl and Disease Activity Ramentioning
confidence: 81%
See 1 more Smart Citation
“…Anticaridiolipin antibodies were present in a larger proportion of RF-positive than RF-negative patients in one study [34], but there was no relationship between them in others [19,35].…”
Section: Association Between Presence Of Acl and Disease Activity Ramentioning
confidence: 81%
“…In 1987 Keane et al [34] reported significantly higher proportion of males, extra-articular manifestations of RA and medial levels of C-reactive protein (CRP) among aCL-positive patients than in the aCL-negative group of RA patients. However, no significant difference was found between two groups with respect to duration, age of onset or functional class of the disease, or the presence or absence of radiologically confirmed erosive joint disease.…”
Section: Association Between Presence Of Acl and Disease Activity Ramentioning
confidence: 99%
“…It has since become clear that aCL antibodies may be demonstrable in a variety of conditions that include other "autoimmune" diseases (23)(24)(25)(26)(27)(28)(29) and infections, particularly viral and spirochetal infections (30). They may also be induced by certain drugs such as chlorpromazine and procainamide (31)(32)(33).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results haven been found in RA patients in which the prevalence of aCL antibodies has been estimated at about 30%; nevertheless, thrombotic manifestation in these patients is a rare clinical condition. 36 Although some researchers have postulate d that RF could be a protecting factor against thrombotic phenomena, there is no strong evidence to support the hypothesis. 37 However, it is important to know the mechanism by which the aCL antibodies are generated in those patients and further investigation s are needed.…”
Section: Discussionmentioning
confidence: 99%